Analisis Ancaman Siber dan Persiapan Pemuda Karang Taruna Kelurahan Rengas dalam Menghadapi Risiko Keamanan Siber - Putra, Jordy Lasmana; Raharjo, Mugi; Fitri, Evita (LPkM Universitas Bakrie, 2024)
Karang Taruna Kelurahan Rengas Ciputat Timur is a social organization for the development of young people who are able to display their character through creation, taste, passion and work in the field of social welfare. The problems faced by Karang Taruna Kelurahan Rengas Ciputat Timur are the lack of skills, security Awareness, human resources, access to training resources and the lack of special training related to Cyber security Awareness so that the youth of Karang Taruna Kelurahan Rengas Ciputat Timur experience blindness to the importance of cyber security which can have fatal consequences in the use of technology in the current era. The purpose of this community service activity is to introduce and provide training related to cyber security awareness to youth organizations in Rengas Village. As for this community service, material is given to youth groups related to cyber security awareness and tips are given in carrying out all daily activities by paying attention to this security. The method used in this community service activity is to provide material using the lecture method by carrying out several stages including preparation, implementation and evaluation of activities. The results of the implementation of this community service activity found that 76.92% stated that the participants gave a fairly good response to the implementation of this community service activity.